Gingival Squamous Cell Carcinoma: a Case Report - Luiz Antonio Guimarães Cabral; Luis Felipe das Chagas e Silva de Carvalho; José Antônio Pereira Salgado; Adriana Aigotti Haberbeck Brandão; Janete Dias Almeida (Stilus Optimus, 2010)
Background: Squamous cell carcinoma is a malignant epithelial neoplasm characterized by variable clinical manifestations. When located in the gingiva, this neoplasm may mimic common inflammatory lesions. The aim of this study was to report a case of atypical squamous cell carcinoma, in which the patient had no risk factors for the development of this neoplasm.Methods: A 61 year old Caucasian female was seen with a 3 month history of a rapidly growing, painful nodule in the gingiva adjacent to tooth #11. Clinical examination revealed a proliferative lesion in the vestibular marginal gingiva of teeth #11 and #12, presenting with purulent exudation. Thus, in view of the clinical symptoms and differential diagnosis of an infectious granulomatous process and malignant neoplasm, an incisional biopsy was obtained from the lesion.Results: The diagnosis of squamous cell carcinoma was made and fourteen days after incisional biopsy, healing was found to be unsatisfactory. The patient was referred for treatment consisting of surgical excision of the tumour. A removable partial denture was fabricated for rehabilitation, one month after surgery of the maxilla; the patient was submitted to dissection of the regional lymph nodes and radiotherapy for an additional 3 months. Three years after the end of treatment, the patient continues to be followed-up and does not show any sign of recurrence.Conclusions: Gingival squamous cell carcinoma is a condition which chance of cure is higher when carcinomatous lesions are diagnosed and treated early. In this instance dentists play an important role in early detection of gingival squamous cell carcinoma.